Cancioncillas dialogadas - Frenk, Margit (El Colegio de México, 2012)
A global study of old Spanish songs consisting of a dialogue between twovoices, mostly without any narrative frame. Citing and analizing numeroustexts, the study covers the following aspects: relation between speakers, contents,themes and situations of the dialogues, as well as friendly versus hostileexchanges. Certain very rural dialogues are focused, as well as rhymesrecited or sung by children in their games.